âYou Donât Have To Be Innovative In the Creative Industriesâ A Study of Entrepreneurial Orientation and Social Capital in Creative Industries - Wardani, Dewi Kusuma; Noviani, Leny; Sabandi, Muhammad; Setyowibowo, Feri (Proceeding of International Conference on Teacher Training and Education, 2016)
Competitiveness and performance of businesses in the creative industry have the disadvantage of resourcemanagement and development and entrepreneurial policies. Creative industries covering the fashionindustry, design, and craft are industries that expected to be able to competewith the establishment of theAsian Economic Community (AEC) by 2015. To improve the capability to compete in the regionally andglobally, internal capabilities such as Entrepreneurial Orientation (EO) and social capitals (SC) ofcompanies in the creative industry need to improve. Entrepreneurial Orientation has been the focus ofmany researchers and contributed significantly to the development of entrepreneurship literature over thedecades. This fact supported by empirically significantfindings contributedby various researchersin theliterature. However, up to the date there are many debates and require more research, specifically in therobustness of the dimensions within creative industries. The current research using Mixed Methodsanalyses tested the EO and SC model to 60 entrepreneurs in the creative industries within specific areasoffashion, design and crafting in Central Java regions. Findings suggested that in the creative industries, EOvaried to those companies in manufacturing and technology industries. The current research contributed tothe literatureby (1) modelling the EO in the creative industry, (2) confirming previous research findings onEntrepreneurship Orientation, (3) suggesting the source of competitive advantage in this industry, (4)social capital not adopted scientifically.However, these findings should require more extensive researchand tested across regions. Hence, the directions for future research are implied in the research limitationssection.